Reliable comparison of perovskite solar cell performance using maximum power point tracking - Rakocevic, Lucija; Ernst, Felix; Gehlhaar, Robert; Aernouts, Tom; Brabec, Christoph; Poortmans, Jef (International Conference on Hybrid and Organic Photovoltaics, 2019)
Organometallic halide based thin film PV has achieved research device efficiencies of 23.7 %, surpassing other thin film PV technologies in less than a decade of research. However, hysteretic behavior caused by ion movement in perovskite semiconductor affecting charge carrier extraction can inhibit a reliable performance measurement. This behavior, reflected in transient current variations following voltage alteration, can be dependent on preconditioning of the sample, scan rate, temperature and the composition of the perovskite solar cell stack itself. Therefore, a reliable performance comparison of perovskite solar cells is non-trivial. We examine the robustness of maximum power point tracking (MPPT) using three measurement algorithms to compare the performance of three n-i-p planar perovskite stacks. Moreover, we extract the relevant measurement parameters for a reliable MPPT. Figure shows how the measurement delay affects the measured performance of a solar cell for each of the studied algorithms. As the result of the study, we propose a measurement protocol to determine the device PCE applicable in everyday laboratory testing of perovskite solar cells. Finally, we draw attention to the importance of defining a robust and universal measurement procedure for comparison of various perovskite based thin film PV devices researched in the community<br